Enhancing executive functioning among toddlers in foster care with an attachment-based intervention. (12th April 2017) - Lind, Teresa; Lee Raby, K.; Caron, E. B.; Roben, Caroline K. P.; Dozier, Mary
Abstract: Young children in foster care often experience adversity, such as maltreatment and lack of stability in early caregiving relationships. As a result, these children are at risk for a range of problems, including deficits in executive functioning. The Attachment and Biobehavioral Catch-up for Toddlers (ABC-T) intervention was designed to help foster parents behave in ways that promote the development of young children's emerging self-regulatory capabilities. Participants included 173 parent–toddler dyads in three groups: foster families that were randomly assigned to receive either the ABC-T intervention ( n = 63) or a control intervention ( n = 58), as well as low-risk parent–toddler dyads from intact families ( n = 52). At a follow-up conducted when children were approximately 48 months old, children's executive functioning abilities were assessed with the attention problems scale of the Child Behavior Checklist (Achenbach & Rescorla, 2000) and a graded version of the Dimensional Change Card Sort developed for preschoolers (Beck, Schaefer, Pang, & Carlson, 2011). Results showed that foster children whose parents received the ABC-T intervention and low-risk children never placed in foster care had fewer parent-reported attention problems and demonstrated greater cognitive flexibility during the Dimensional Change Card Sort than foster children whose parents received the control intervention. These results indicate that an attachment-based intervention implemented among toddlers in foster care is effective in enhancing children's executive functioning capabilities.